Electrospinning repellents in polyvinyl alcohol-nanofibres for obtaining mosquito-repelling fabrics. Issue 8 (14th August 2019) - Ciera, Lucy; Beladjal, Lynda; Van Landuyt, Lieve; Menger, David; Holdinga, Maarten; Mertens, Johan; Van Langenhove, Lieva; De Clerk, Karen; Gheysens, Tom
Abstract : Recently, the use of repellents for preventing the transmission of mosquito-borne diseases is getting increasingly more attention. However, most of the current repellents are volatile in nature and must be frequently re-applied as their efficacy is only limited to a short period of time. Therefore, a slow release and abrasion-resistant mechanism is needed for prolonging the protection time of the repellents. The focus of this study is on the direct micro-encapsulation of repellents from an emulsion and integration of already encapsulated repellents into nanofibres via electrospinning. Different repellents were electrospun in polyvinyl alcohol (PVA) nanofibrous structures, namely p -menthane-3, 8-diol micro-capsules, permethrin, chilli and catnip oil. The repellents were successfully incorporated in the nanofibres and the tensile properties of the resulting samples did not have a significant change. This means that the newly created textiles were identical to current PVA nanofibrous textiles with the added benefit of being mosquito repellent. Principally, all incorporated repellents in the nanofibrous structures showed a significantly reduced number of mosquito landings compared to the control. Consequently, the currently described method resulted in a new and very effective repelling textile material that can be used in the prevention against mosquito-associated diseases.